Análisis del uso de un blog de aprendizaje educativo de la asignatura de ciencias naturales en la Unidad Educativa Oriente Ecuatoriano, año 2021 - Bonoso Conforme, Jeffrey Alexander (2021)
With the development of generation and the area that the net occupies in normal existence, it is crucial to recognize the wide variety of possibilities it offers in all regions of our life, the mastery and acquisition of new technological didactic strategies of instruction that includes the blog makes teachers use it to dynamize the training-learning system, reaching a dynamic liking in a common theme that can be treated by all participants in the classroom. Existing studies work with the objective of obtaining results that show how beneficial the internet is within the development of student sport, and what number of students make use of the blog for their school performance. The blog is a vital resource for the instructor, by means of this software it is going to be viable to talk about and analyze the doubts acquired in the magnificence paintings and to be able to be solved by means of alternating thoughts, teamwork, layout, instantaneous visualization of what is produced, and many others, so a giant learning is obtained based mostly on the investigative and experimental. This field and bibliographic research has a qualitative technique through the descriptive and exploratory method with the socio-educational modality, the interviewed population is five teachers of the CCNN area of the Educational Unit Oriente Ecuatoriano, which has a portable laboratory ready, with the purpose of making a contribution to the development and implementation of inspiration to create an educational blog to increase the way to train-study the problem of Natural Sciences, with a good enough processing of understanding and generate a great learning that translates into warm and satisfactory temperature of training.